Evapotranspiration and Water Balance of Maize - Sheelavantra, M N; Ratnam, B P; Tilve, N S (Annals of Arid Zone, 2016)
Evapotranspiration studies were made on maize during the kharif season of the years 1980 to 1987 at Dharwad by using gravimetric lysimeters. The seasonal total ET was 339.7 mm with a daily mean of 2.4 mm. Water balance computation indicated that the maize crop can be raised during kharif season wilhout moisture stress and irrigation. The water use efficiency was 17.78 kg/ha/mm.